Job Satisfaction and Professional Burnout in Kindergarten Teachers - Mandarić Vukušić, Anita; Krstulović, Valentina (Revija za elementarno izobraževanje, 2024)
The article investigates the relationship between kindergarten teachers’ professional burnout and their education level and work experience. The data were obtained through a survey conducted among 206 kindergarten teachers. According to the results, kindergarten teachers are most satisfied working with children and collaborating with colleagues, and least satisfied with their monthly income, formal professional training offer, working conditions and work organization. Self-assessment of work exhaustion and work alienation showed no statistically significant differences, but a difference was recorded for work engagement. Kindergarten teachers with bachelor’s degree have the highest level of work engagement, as well as those who are at the beginning of their careers.
Keywords: professional training; work role; work conditions; kindergarten teachers